From Forced to Accustomed: Lessons from the Pandemic about Teacher Readiness in Online Learning - Ika Febrian Kristiana; Unika Prihatsanti; Costrie Ganes Widayanti (International Journal Labs, 2022)
In the last two decades, educational institutions around the world have massively implemented technology in learning, but there is no full implementation of distance learning in its application. The pandemic has dramatically made a full shift from face-to-face learning to online-based distance learning. It can be said that teachers are no exception in Indonesia experiencing a disrupting phase in carrying out the main task of learning. This qualitative study aims to explore teacher readiness in implementing online learning policies. The research questions are 1) How is the psychological response (cognitive, affective, and behavioral) of teacher readiness; 2) What are the determinants of the readiness of teachers to carry out online learning. A total of 19 primary school teacher participants from several regions in Indonesia (M age = 39; Female = 73.68%; Male = 26.32%) were involved in online FGDs. The data analysis follows the stages of the thematic analysis of Braun and Clarke (2016). Five final themes were obtained that describe the psychological response of teachers' readiness to implement online learning: adaptation of online teaching behavior, planning and implementation of learning, teacher dedication, obstacles and constraints, and teacher expectations in online learning.